Nanoemulsion Improves the Anti-Inflammatory Effect of Intraperitoneal and Oral Administration of Carvacryl Acetate - Rafael Limongi de Souza; Luíza Carolina França Opretzka; Mayara Castro de Morais; Camila de Oliveira Melo; Brunna Emanuelly Guedes de Oliveira; Damião Pergentino de Sousa; Cristiane Flora Villarreal; Elquio Eleamen Oliveira (MDPI AG, 2023)
Carvacryl acetate (CA) is a monoterpene obtained from carvacrol, which exhibits anti-inflammatory activity. However, its low solubility in aqueous media limits its application and bioavailability. Herein, we aimed to develop a carvacryl acetate nanoemulsion (CANE) and assess its anti-inflammatory potential in preclinical trials. The optimized nanoemulsion was produced by ultrasound, and stability parameters were characterized for 90 days using dynamic light scattering after hydrophilic-lipophilic balance (HLB) assessment. To evaluate anti-inflammatory activity, a complete Freund's adjuvant-induced inflammation model was established. Paw edema was measured, and local interleukin (IL)-1β levels were quantified using ELISA. Toxicity was assessed based on behavioral changes and biochemical assays. The optimized nanoemulsion contained 3% CA, 9% surfactants (HLB 9), and 88% water and exhibited good stability over 90 days, with no signs of toxicity. The release study revealed that CANE followed zero-order kinetics. Dose-response curves for CA were generated for intraperitoneal and oral administration, demonstrating anti-inflammatory effects by both routes; however, efficacy was lower when administered orally. Furthermore, CANE showed improved anti-inflammatory activity when compared with free oil, particularly when administered orally. Moreover, daily treatment with CANE did not induce behavioral or biochemical alterations. Overall, these findings indicate that nanoemulsification can enhance the anti-inflammatory properties of CA by oral administration.